2013
DOI: 10.1002/chem.201202657
|View full text |Cite
|
Sign up to set email alerts
|

Am(m)ines Make the Difference: Organoruthenium Am(m)ine Complexes and Their Chemistry in Anticancer Drug Development

Abstract: With the aim of systematically studying fundamental structure-activity relationships as a basis for the development of Ru(II) arene complexes (arene = p-cymene or biphenyl) bearing mono-, bi-, or tridentate am(m)ine ligands as anticancer agents, a series of ammine, ethylenediamine, and diethylenetriamine complexes were prepared by different synthetic routes. Especially the synthesis of mono-, di-, and triammine complexes was found to be highly dependent on the reaction conditions, such as stoichiometry, temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…The geometrical parameters of the complex are in agreement with previously determined structures of compounds, which vary only in the nature of the N‐donor ligands 32. 33 The average RuC bond length in 6 is 2.186 Å, whereas RuCl1, RuCl2 and RuN distances are 2.4194(4), 2.4026(4), and 2.1368(12) Å, respectively (in comparison for [Ru(η 6 ‐ p ‐cymene)Cl 2 (NH 3 )], RuC av 2.170(8), RuCl1 2.4157(6), RuCl2 2.4157(6), and RuN 2.130(3) Å) 32. The crystal structure of 6 was employed as the starting point for subsequent docking studies.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The geometrical parameters of the complex are in agreement with previously determined structures of compounds, which vary only in the nature of the N‐donor ligands 32. 33 The average RuC bond length in 6 is 2.186 Å, whereas RuCl1, RuCl2 and RuN distances are 2.4194(4), 2.4026(4), and 2.1368(12) Å, respectively (in comparison for [Ru(η 6 ‐ p ‐cymene)Cl 2 (NH 3 )], RuC av 2.170(8), RuCl1 2.4157(6), RuCl2 2.4157(6), and RuN 2.130(3) Å) 32. The crystal structure of 6 was employed as the starting point for subsequent docking studies.…”
Section: Resultssupporting
confidence: 87%
“…The detection of complexes with coordinated monodentate N‐donor ligands can be challenging with ESI‐MS and indicates limited complex stability under the ESI spraying conditions 31. 32 However, this does not reflect the situation in solution. Interestingly, such ions were not observed for the complexes with aminohexanoic spacers (i.e., 8 and 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…The higher cytotoxicities of complex 3 and 6 may also be related to their faster rate of hydrolysis. It has been reported that hydrolysis of the RuCl bond of Ru II –arene complexes are important for their activation, forming the aqua products that bind to DNA or protein 21b. 24…”
Section: Resultsmentioning
confidence: 99%
“…Only RAPTA, which is an organoruthenium drug candidate with antimetastatic properties, [9] was assayed in as imilar setting Hydrolyzed ruthenium-arene metallodrugs face innumerous potential binding partners intracellularly.T arget profiling by affinity purification is suitable to profile for potential targets by immobilizing ad rug on solid support and exposing it to whole cell lysates.…”
mentioning
confidence: 99%